Performance of different types of controllers in tracking optimal temperature profiles in batch reactors - Aziz, N.; Hussain, Mohd Azlan; Mujtaba, I.M. (Computers & Chemical Engineering, 2000)
Performance of three different types of controllers in tracking the optimal reactor temperature profiles in batch reactor is considered hear. A complex exothermic batch reaction scheme is used for this purpose. The optimal reactor temperature profiles are obtained by solving optimal control problems off-line. Dual mode (DM) control with proportional-integral (PI) and proportional-integral-derivative (PID) and generic model control (GMC) algorithms are used to design the controllers to track the optimal temperature profiles (dynamic set points). Neural network technique is used as the on-line estimator the amount of heat released by the chemical reaction within the GMC algorithm. The GMC controller coupled with a neural network based heat-release estimator is found to be more effective and robust than the PI and PID controllers in tracking the optimal temperature profiles to obtain the desired products on target.